Regulation of Axillary Meristem Initiation by Transcription Factors and Plant Hormones - Yang, Minglei; Jiao, Yuling (Frontiers in Plant Science, 2016)
One distinctive feature of plant post-embryonic development is that plants can undergo reiterative growth and continuous organogenesis throughout their lifetimes. Axillary meristems (AMs) in leaf axils play a central role in this growth and differences in meristem initiation and development produce the diversity of plant architecture. Studies in the past 15 years have shown that several transcription factors (TFs) and phytohormones affect AM initiation. In this review, we highlight recent research using systems biology approaches to examine the regulatory hierarchies underlying AM initiation and the role of auxins and cytokinins in AM initiation and development. This research revealed a developmental mechanism in which phytohormone signals act with a gene regulatory network containing multiple TFs to contribute to the initiation of AMs.